The Anatolian Journal of Cardiology 2021
DOI: 10.5152/anatoljcardiol.2021.28303
|View full text |Cite
|
Sign up to set email alerts
|

A seven-year single-center experience on AngioJet rheolytic thrombectomy in patients with pulmonary embolism at high risk and intermediate-high risk

Abstract: Objective: AngioJet rheolytic thrombectomy (ART) has been used as a catheter-based treatment for acute pulmonary embolism (PE). In this study, based on our 7-year experience with ART in patients with PE, we evaluated the efficacy and safety outcomes of ART. Methods: Our study is based on retrospective evaluation of 56 patients with high-and intermediate-high-risk PE, with an average age of 62 years [interquartile range (IQR) 50-73 years] who underwent ART. Results: High and intermediate-high risks were noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
17
2
Order By: Relevance
“…Although postprocedural renal deterioration was observed in 39.3% of patients, 1-session dialysis was required in only 1 (1.8%) patient. These current data suggest that safety issues of rheolytic thrombectomy may be re-evaluated 33 .…”
Section: Rheolytic Thrombectomymentioning
confidence: 83%
“…Although postprocedural renal deterioration was observed in 39.3% of patients, 1-session dialysis was required in only 1 (1.8%) patient. These current data suggest that safety issues of rheolytic thrombectomy may be re-evaluated 33 .…”
Section: Rheolytic Thrombectomymentioning
confidence: 83%
“…The CT measures of RV/LVr, QS, PA diameters, and echocardiographic measures of TAPSE and pulmonary artery systolic pressure (PAPs) estimates were significantly improved after the reperfusion treatments including USAT, rheolytic thrombectomy, and IV tPA infusions ( Table 2 ). 11 - 14 …”
Section: Resultsmentioning
confidence: 99%
“…The AngioJet System creates a local low-pressure zone to entrain, fragment, and aspirate thrombi via Bernoulli's principle of fluid dynamics. The largest and latest 7-year single-center study on AngioJet rheolytic thrombectomy in patients with PE revealed that for patients with PE who have various comorbidities and a proclivity to bleed, ART may be considered preferable, resulting in significant improvements in obstructive burden and hemodynamics (8). ART mentioned in most cases or articles (8,11), instead of using the pulse spray technique and t-PA assisted in increasing the surface area of thrombus to enhance the effectiveness of lytic agents, we chose thrombus fragmentation and aspiration techniques with no lytic agents for this patient who had absolute contraindications to thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with fatal bleeding risks such as recent surgical procedures, intracranial hemorrhage, and other contraindications to thrombolysis, anticoagulation, or surgical thrombectomy; the treatment options are of controversial complexity. The AngioJet rheolytic thrombectomy (ART) system provides pharmacomechanical thrombolysis and has been previously attempted for PE, with promising clinical outcomes despite several adverse events reported (5)(6)(7)(8). Nowadays, transportable extracorporeal membrane oxygenation (ECMO) assistance systems with percutaneous femoral cannulation may become effective in extreme circumstances, maintaining circulation and oxygenation.…”
Section: Introductionmentioning
confidence: 99%